The integration process of small and medium sized enterprises (SMEs) in Turkey to the european union a comparative analyses between Turkey and Italy - Bulak, İdil (My University, 2005)
Bu tezin amacı Türkiye’deki KOBİleri AB’ye entegrasyon sürecinde İtalya ile karşılaştırmalı olarak incelemektir. Öncelikle KOBİ tanımının netlik kazanması için girişimcilik kavramı üzerinde durulmuştur. Girişimciliği oluşturan temel taşlar anlatılmış, girişimcilik ile KOBİler arasında pozitif ilişki olduğu belirtilmiştir. Daha sonra AB’nin KOBİ tanımı yapılmış, Türkiye’deki KOBİ tanımlarından örnekler verilmiştir. Türkiye ve AB’deki şu anki KOBI yapısı sergilenmiş, KOBİlerin sorunları, güçlü ve zayıf yönleri, avantajları, dezavantajları üzerinde durulmuştur. Yasal açıdan KOBİlerin maruz kaldığı sorunlar detaylı olarak incelenmiştir. KOBİlerin tarihsel gelişimi, önem kazanmasına neden olan olaylar ve gelişmeler üzerinde durulmuş, özellikle KOBİlerin önem kazanmasındaki üç stratejik sebep belirtilmiş ve açıklanmıştır. AB tarihinde sanayi ve KOBİ politikalarının gelişimi anlatılmış, dünü, bugünü, yarını kapsayacak biçimde gösterilmiştir. İkinci bölüm daha çok KOBİleri destekleyen teşviklere ayrılmıştır. AB’nin çokyıllı olmak üzere, çeşitli konu başlıkları altındaki teşvik araçlarına,girişimlere ve fonların açıklanmasına yer verilmiştir. Daha sonra AB’nin Türk KOBİlerini yararlandırdığı teşvik enstrümanları açıklanmıştır. Diğer bir önemli konu da KOBİlerin finansmana erişimidir. KOBİlerin finansmanı dışsal finans ve içsel finans olarak ikiye ayrılmıştır. Dışsal kaynaklar da banka ve banka dışı olmak üzere iki bölümde incelenmiştir. Gümrük Birliği’nin KOBİler üzerine etkileri altı başlık altında anlatılmıştır. Üçüncü bölüm olan karşılaştırma bölümünde ise belirlenen oniki karşılaştırma kriteri üzerinden İtalya ve Türkiye KOBİleri incelenmiştir. Son olarak tüm bu yapılanlar sonuç bölümünde toparlanmış ve görüşler belirtilmiştir.

The main aim of this thesis is to analyse Turkish SMEs, in the integration process of Turkey to the EU and to make a comparison with the case of Italy. First of all, in order to clarify the definition of SMEs, the researcher has aimed at explaining ‘entrepreneurship’ concept together with the basic elements of entrepreneurship. It is asserted that there is a positive relation between entrepreneurship and SMEs. Then; EU’s SME definition has been made and some definitive examples from Turkey have been provided. Afterwards; the recent structure of SMEs both in the EU and in Turkey has been analysed. The problems, weaknesses, strengths, advantages and disadvantages of SMEs have been explained; and the problems deriving from legal points, have been analysed in detail. Later on; the historical development of SMEs and the reasons which made SMEs important, have been discussed. Some reasons increasing the importance of SMEs have been displayed in particular. The development of the industry and SME policies in the history of the EU has been explained including the strategies of past, present and the future. Following chapter has mainly focused on incentive mechanisms about SMEs. Funds and all other incentive mechanisms under different headings have been explained in detail. Then, instruments of the EU for Turkish SMEs have been explained. Another important issue is the ‘access of SMEs to finance’. The finance of SMEs has been divided into two: External Finance which has also been divided into two, as; financing from banks and financing from other external sources, and Internal Finance. Following this section, the effects of Customs Union on Turkish SMEs has been explained under six headings. The last chapter deals with the comparison of Turkey with Italy. In order to compare these two countries, twelve criteria have been used. Finally, all these topics have been compiled up and various opinions have been provided about the issue.
Keywords: Avrupa Birliği; Ekonomi